Efforts to Improve Student Learning Outcomes in Islamic Education Learning by Implementing the Discovery Learning Model at SMA Negeri 1 Kluet Tengah - Wirdatul Jannah; Nur Azizah (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to improve students’ learning outcomes in Islamic Education through the implementation of the Discovery Learning model at SMA Negeri 1 Kluet Tengah. The research employed Classroom Action Research (CAR) consisting of two cycles, with each cycle including planning, action, observation, and reflection stages. The participants were 32 eleventh-grade students. Data were collected through achievement tests, observation sheets, and documentation. Quantitative data were analyzed using descriptive statistics to measure the improvement of students’ cognitive learning outcomes, while qualitative data were analyzed to examine changes in student engagement and participation during the learning process. The findings indicate a significant improvement in students’ learning outcomes after the implementation of the Discovery Learning model. In the pre-cycle stage, only 46.88% of students achieved the minimum mastery criterion (MMC) with a mean score of 68.75. In Cycle I, mastery increased to 71.88% with a mean score of 76.34. The improvement became more substantial in Cycle II, where 90.63% of students met the MMC with a mean score of 84.21. Observational data also showed enhanced student engagement, critical thinking, and collaborative participation during learning activities. The results demonstrate that the Discovery Learning model effectively fosters active learning, conceptual understanding, and higher-order thinking skills in Islamic Education. This study contributes empirically to the growing body of research supporting student-centered pedagogical approaches in Islamic Education at the secondary school level. It is recommended that Islamic Education teachers integrate Discovery Learning strategies systematically to enhance both cognitive achievement and student engagement.